2010
DOI: 10.1111/j.1365-2125.2009.03559.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral clotrimazole troches on the pharmacokinetics of oral and intravenous midazolam

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• Clotrimazole troches are commonly used as prophylaxis for thrush that may develop in immunocompromised patients.• Conflicting data suggest that clotrimazole may induce or inhibit cytochrome P450 (CYP) 3A4. WHAT THIS STUDY ADDS?• We have demonstrated that clotrimazole increased the area under the concentration-time curve and decreased the apparent oral clearance of midazolam following oral administration without affecting the pharmacokinetic properties of midazolam afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…In total, 38 and 44 publications that included reported CL values were identified for gentamicin and midazolam, respectively. These papers reported a total of 66 and 57 CL values for gentamicin and midazolam, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 38 and 44 publications that included reported CL values were identified for gentamicin and midazolam, respectively. These papers reported a total of 66 and 57 CL values for gentamicin and midazolam, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Among all significant covariates, BMI correlated positively with SRL log (C/D), similar to a previous finding showing higher initial tacrolimus blood levels in overweight renal transplant recipients (22). Additionally, SRL concentration/dose ratios were increased during clotrimazole or statins co-administration and were decreased during tacrolimus or prednisone co-administration, suggesting CYP3A enzyme competition between substrates (statins and tacrolimus) as well as CYP3A induction and inhibition by corticosteroids (23,24) and clotrimazole, respectively (25,26). The effect of steroids may influence the observation that prednisone sparing sirolimus protocols have high rates of SRL related adverse effects such as mouth ulcers (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…4 However, the drug interaction has gained attention since Shord et al recently reported that clotrimazole troche inhibited the intestinal metabolism of midazolam, a substrate drug for CYP3A, without affecting the systemic metabolism. 5 In the current case, the CL/F of everolimus increased by 1.9-fold after clotrimazole discontinuation. Everolimus is metabolised by CYP3A in the liver and intestines.…”
mentioning
confidence: 51%
“…It was previously assumed that systemic absorption of clotrimazole troche is minimal and that the risk of drug interactions with CYP3A substrates is low . However, the drug interaction has gained attention since Shord et al recently reported that clotrimazole troche inhibited the intestinal metabolism of midazolam, a substrate drug for CYP3A, without affecting the systemic metabolism . In the current case, the CL/F of everolimus increased by 1.9‐fold after clotrimazole discontinuation.…”
mentioning
confidence: 60%